PENGARUH INTENSITAS BERMAIN GAME PUBG DAN PENGAWASAN ORANG TUA TERHADAP PERILAKU AGRESIF VERBAL REMAJA - Atasa Yudha Ergana; Agus Naryoso; Primada Qurrota Ayun (Interaksi Online, 2022)
Verbal aggressive behavior is violence with communication aimed at people, carried out intentionally with the intention of hurting, intimidating, and harming others indirectly or directly (Nindya and Margaretha, 2012: 2). There are several factors that make a person perform verbal aggressive behavior, especially in adolescents, namely the intensity of playing PUBG games and parental supervision. The intensity of playing the PUBG game can be concluded, namely the depth of an activity carried out with pleasure over the media that has a benchmark for how often a person plays the game within a certain period of time. Parental supervision is an effort that has a coercive nature on the emotional and psychological development of adolescents such as self-disclosure, thinking, emotions that are expressed into adolescent expressions and the closeness of parents. The theory used in this research is social learning theory and parental mediation. This study aims to determine the effect of the intensity of playing PUBG games and parental supervision on adolescent verbal aggressive behavior. The research population used is people aged 16-24 years, domiciled in the city of Semarang, and an unknown number of people play PUBG games. The sample is 60 respondents using non-probability sampling technique and purposive sampling method. This type of research uses explanatory. Data analysis using multiple linear regression analysis where there is a significant t test, f test, and coefficient of determination with SPSS 25 for Windows application. Using quantitative methods with a positivistic paradigm. The results of the t-test showed that the intensity of playing the PUBG game had an effect on the verbal aggressive behavior of adolescents with a sig value of 0.000 0.050. The results of the research on the f test showed that the intensity of playing the PUBG game and parental supervision has an effect on adolescent verbal aggressive behavior with a sig value of 0.00> 0.050. The results on the coefficient of determination, the influence of the intensity of playing PUBG games and parental supervision on adolescent verbal aggressive behavior have an R Square value of 0.289 with the meaning that the influence value is 28.9%.